The preparation and study of Bis(pyridyl-imine) and Monohelical salen-type complexes of iron and zinc - Wiznycia, Alexander V. (Kansas State University, 2006)
In the field of asymmetric catalysis salens and related molecules occupy a unique position in the breath and scope of reactions facilitated. They, nonetheless, are characterized by several conformationally derived limitations. This work deals with applying the principles of helicity with the goal of remedying these shortcomings, thereby ultimately fashioning, better, more selective catalysts. A series of novel ligands bearing phenanthryl and benz[a]anthryl side-arms attached to either a cyclohexyl or binaphthyl backbone bridging group, were prepared via multi-step synthesis. The ligands were subsequently metallated with zinc and iron salts to afford neutral helimeric complexes, that were characterized in the solution and solid states. The binaphthyl complexes were found via X-ray crystallographic analysis to afford exclusively M-helimers, while those incorporating a cyclohexyl bridge gave predominantly 1 : 1 P + M mixtures. A significantly greater degree of side-arm overlap was apparent where benz[a]anthryl side-arms were employed. 1H NMR analysis, unfortunately, did not allow for solution phase helimer determination, and ECD spectroscopy was therefore utilized as an alternative. In conjunction with computational techniques the conformations were probed, and to a high degree of certainty the prevailing solution geometries of the cyclohexyl complexes predicted. Our results indicate that in solution the M configuration is the sole or dominant form. Ionic zinc complexes based upon a tetradentate nitrogen donor motif and 8-isopropyl-2-quinolinecarboxaldehyde were also prepared. Structural characterization of the zinc complexes showed each to bind to two ZnCl2 units, and as a consequence to form dinuclear helicates.
Keywords: SALEN; CATALYSIS; ORGANIC; CHEMISTRY; HELICAL; Chemistry, Inorganic (0488); Chemistry, Organic (0490)